Left ventricular unloading before percutaneous coronary intervention is associated with improved survival in patients with acute myocardial infarction complicated by cardiogenic shock. (14th October 2021) - Miyashita, S; Marbach, J; Banlengchit, R; Kapur, N
Abstract: Background: Left ventricular unloading with Impella before percutaneous coronary intervention (PCI) may improve survival outcomes in patients with acute myocardial infarction complicated by cardiogenic shock (AMI-CS). However, the optimal timing to initiate Impella remains controversial. Purpose: We conducted a systematic review and meta-analysis to compare survival outcomes of patients supported with Impella before PCI (pre-PCI) with those supporte after (post-PCI). Methods: This study was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2009 guidelines. Multiple databases were searched through March 2021. All studies evaluating the impact of pre-PCI versus post-PCI Impella placement in patients with AMI-CS were included. A composite primary endpoint included in-hospital, 30-day, and 6-month survival rates. Results: We identified five observational studies comparing outcomes in 432 patients with AMI-CS, including 173 patients treated with Impella pre-PCI and 259 patients post-PCI. In the pooled analysis, patients in the pre-PCI group had significantly lower in-hospital mortality compared to patients in the post-PCI group (RR 0.62, 95% CI: 0.50–0.76, I 2 =0%). Reduced mortality rate in the pre-PCI group persisted through 30-days (HR 0.61, 95% CI: 0.47–0.80, I 2 =0%) and at 6-months (HR 0.67, 95% CI: 0.45–0.99, I 2 =0%). There was no difference in the risk of adverse events including re-infarction, stroke, major bleeding, acute ischemic limb, access site bleeding, and hemolysis. Conclusion: In a meta-analysis of studies evaluating mortality among AMI-CS patients treated with primary versus bailout left ventricular support, Impella placement prior to PCI was associated with improved survival. FUNDunding Acknowledgement: Type of funding sources: None.